Differential benefits of internet-based behavioral activation (iBA) for adolescents with high vs. low reward probability: a secondary analysis - Kim, Ye-Seul; Lee, Eunbyeol; Choi, Kee-Hong (Frontiers in Psychology, 2025)
IntroductionBehavioral activation (BA) therapy is effective in treating depression in both adults and adolescents, and internet-based BA (iBA) therapy showed promise during the COVID-19 pandemic. Adolescents with depression often exhibit motivational impairment, which is associated with reduced motivation and engagement in rewarding activities as well as a heightened risk of problematic internet use. This study examined the differential benefits of iBA in alleviating depressive symptoms in adolescents with relatively high and low Reward Probability Index (RPI) levels.MethodsUsing a randomized controlled trial design, this secondary analysis included 38 adolescents diagnosed with major depressive disorder, who were randomly assigned to either the iBA or internet-based psychoeducation and supportive therapy (iST) groups. Depressive symptoms, BA levels, and RPI were assessed at pre-treatment, post-treatment, and the 3-month follow-up.ResultsThe findings revealed that adolescents with low baseline RPI who received iBA showed a significantly greater reduction in depressive symptoms than those with high baseline RPI. Additionally, adolescents with low baseline RPI in the iBA group showed a significantly greater reduction in depressive symptoms than those in the iST group.DiscussionThese results suggest that iBA is particularly beneficial for adolescents with low RPI, especially those experiencing anhedonia, and provides a promising approach to enhance treatment outcomes in this population. High accessibility of iBA may promote engagement in rewarding real-life activities.